Stimuli responsive behavior in a D–A–D organic fluorophore: the role of cold crystallization - Afsar Uddin, Mohammad; Gámez-Valenzuela, Sergio; Ruiz-Delgado, María del Carmen; Gómez-Lor, Berta (The Royal Society of Chemistry, 2025)
Herein, dimethyl-4,7-di(2-thienyl)-2,1,3-benzothiadiazole-5,6-dicarboxylate (DTBTE) is introduced as a highly efficient fluorophore with multi-stimuli responsive properties. Its molecular structure, consisting of a benzothiadiazole (BTD) core functionalized with ester groups and thiophene rings, results in a highly flexible framework with dynamic conformational behavior and low rotational barriers. These characteristics allow DTBTE to exhibit cold crystallization at 80 1C, accompanied by a pronounced and reversible color change. This transition can be reversed, restoring the amorphous state via external stimuli such as solvent fuming or mechanical shearing. Density functional theory (DFT) calculations, combined with advanced characterization techniques such as single-crystal X-ray analysis and IR and Raman spectroscopy, provide detailed insight into the mechanisms driving the phase transformations and their associated color changes. In particular, the flexibility of the ester groups plays a crucial role in enabling cold crystallization, as it facilitates the formation of a complex hydrogen bond network. Additionally, the switchable emission colours are attributed to cis/trans conformational changes in the thiophene groups during the transition between the crystalline and the amorphous phases. These findings highlight DTBTE as a promising platform for designing efficient stimuli-responsive materials and provide valuable guidelines for the development of new fluorophores exhibiting a dynamic behavior.
Keywords: Química física; Luminiscent organic materials; Organic materials; Cold crystallization; Fluorophores